Implementasi Pembelajaran Menggunakan Moodboard pada Pelatihan Desainer Pakaian Kreasi di Balai Pelatihan Vokasi dan Produktivitas (BPVP) Padang - Syamsul, Ria Laster; Ernawati, Ernawati (Jurnal Ilmiah Dikdaya, 2024)
At the learning implementation stage of the Creative Clothing Designer program at BPVP Padang, students found it difficult to find sources of ideas, to design clothing according to the specified concept and design theme, because students came from different scientific backgrounds. Therefore, students are directed to create a moodboard, to make learning easier. This research is aimed at finding out: learning planning, learning implementation and evaluating learning outcomes of training students using moodboards. This research uses a qualitative descriptive research method, using primary and secondary data sources. The number of informants in this qualitative research was not determined, so the informants for this research were 1 instructor and 12 training students (Bungin 2010:53). Data collection techniques, in the form of observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, verification and conclusions (Sugiyono, 2017). The research results show: (1) at the planning stage the instructor carries out learning planning before the learning process begins by creating lesson plans and learning media. (2) At the learning implementation stage, students will learn how to design clothing in various shapes using the help of moodboard media. (3) Meanwhile, at the evaluation stage, the learning outcomes after using the moodboard become more conceptual and students are able to present 4 collections with 4 uses of the moodboard. Where 1 collection is produced, containing 3-4 student works, so the total student work obtained from 4 moodboards is 12 works that have one unified design. The results of this work will be presented at the end of the lesson to prove the relationship between the design and the source of the idea.